Pemetaan Kompetensi Siswa Untuk Mengikuti Seleksi Lomba Kejuruan Multimedia Menggunakan Metode K-Means - Lis Utari; Rio Geraldy (Universitas Binaniaga Indonesia, 2022)
The process of mapping competent students who will take part in the competition is the selection of students who have the best scores in the vocational field, which is carried out by the academic side in order to include students who are competent in the vocational field to be included in the vocational competition. So far, the school still has difficulties in selecting competent and less competent students due to the limitations of the presentation and processing of the data carried out. To facilitate the mapping of competent students in the vocational field, this activity is computerized into software. Time accuracy and effectiveness are important factors so that the mapping process of competent students can run well and as it should. In this research, an application is made that can cluster competent students so that they can take part in Multimedia vocational competitions appropriately and accurately using the K-Means Algorithm. It applies variables such as Academic Values and Attitude Values.